Emerging importance of omega‐3 fatty acids in the innate immune response: Molecular mechanisms and lipidomic strategies for their analysis. Issue 8 (18th February 2013) - Maskrey, Benjamin H.; Megson, Ian L.; Rossi, Adriano G.; Whitfield, Phillip D.; Schneider, Claus
<x xml:space="preserve">Abstract</x> The beneficial health properties of dietary omega‐3 polyunsaturated fatty acids, particularly eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) have long been known and their metabolic dysfunction has been linked to a range of diseases including various inflammatory disorders, cardiovascular diseases, and cancer. However, the molecular mechanisms underlying their health benefits have remained unclear. Recent technological advances in lipidomic analytical strategies have resulted in the discovery of a range of bioactive mediators derived from EPA and DHA that possess potent anti‐inflammatory and pro‐resolving properties and that may be responsible, at least in part, for the beneficial effects observed. These mediators include resolvins, protectins and maresins, as well as EPA derivatives of classical arachidonic acid derived eicosanoids, such as prostaglandin E3. The aim of this review is to provide an overview of the biosynthetic pathways and biological properties of these omega‐3 mediators, with a particular focus on the emerging importance of the counter‐regulatory role of omega‐3 and ‐6 fatty acids in the spatial and temporal regulation of the inflammatory response. It will also provide an insight into a range of lipidomic approaches, which are currently available to analyse these fatty acids and their metabolites in biological matrices.